LAS TRAMAS DE LA VERDAD: CONSIDERACIONES SOBRE LA ENSEÑANZA DE LA HISTORIA - Bermejo Barrera, José C. (Antigüedad y Cristianismo, 1995)
The educative process, according to the more traditional point of view, is simply the transmission of a series of data of an intelectual character. In this paper a study is made of History as Knowledge and how it is the result of a series of institutional, social and ideological events, which vary according to the historical circumstances. These events contribute to the formation of the social reality, the development of which shows us the fundamental importante of the transmission of the knowlege of History, essencial for the definition of the social and national entities from the nineteenth century on.